TOLL-LIKE (TLRS 1,4,5) IMMUNODETECTION OF SOME TOLL-LIKE RECEPTORS AS AN IMMUNE RESPONSE TO PATIENTS WITH ACUTE APPENDICITIS AND ITS EFFACT ON CLINICAL FEATURES IN BASRA/IRAQ - shaker, Zainab Nihad; Mahdi, Dawood S.; Alsaimary, Ihsan Edan; Hoka, Saad Ishaq Iskandar (PT. Antis International Publisher, 2024)
Background: Acute Appendicitis is the most common cause of emergency cases worldwide, and it may have serious consequences. If there is no precise diagnosis, it poses a dreadful issue for the community. Researchers tried to use several markers to determine the definitive diagnosis of Appendicitis. Our research thus sought to determine the various Toll-like receptor TLR1, TLR4, and TLR5 concentrations in the blood of patients suspected of Appendicitis as a diagnostic predictor. Method: This study conducted a case-control analysis on patients diagnosed with Appendicitis in the operating room at Al-Sadr Teaching Hospital and Al-Shifaa Teaching Hospital in Basra, Iraq. The control group was randomly chosen between July 2023 and November 2023. a total of 88 samples were enrolled in the study. Seventy of these samples came from patients experiencing signs and symptoms of Appendicitis. In contrast, the remaining eighteen samples were collected from apparently healthy controls (AHC) who were identical to the patient's group in terms of age, gender, habitat, and other characteristics but did not experience any appendicitis symptoms. Ethical approval was obtained from the Basra Health Department for data collection. Results: According to the findings of this investigation, the immunological markers TLR1 and TLR4 were statistically significant at a level of (P≤0.05) between the serum samples of patients and the control groups. the median concentration of (TLR1 and TLR4) were (14.70 ,10.89 ng/ml) respectively than control group (8.15 ,6.98 ng/ml), statistically show highly significant (P-= 0.000), while the median concentration of TLR5 in appendicitis patients was lower (3.11 ng/ml) than control (3.77 ng), without any significant differences (p=0.185). Conclusion: The serum concentration of TLR1 and TLR4 has the potential to predict the diagnosis of appendicitis.